Mechanical Characterization of Self-Supported Noble Metal Gel Monoliths - Schneider, Kristian; Melnyk, Inga; Hiekel, Karl; Fery, Andreas; Auernhammer, Guenter K.; Eychmueller, Alexander (Journal of Physical Chemistry C, 2019)
Noble metal hydro- A nd aerogels exhibit a variety of unique properties, including large surface areas, ultralow densities, and high porosities. While their potential use in various applications ranging from catalysis to energy storage has attracted attention in recent years, their mechanical properties are largely unknown. Here, through both macroscopic and microscopic rheological methods, we investigated the mechanical properties of these materials on various length scales. Using piezo-rheology, we show that macroscopically the metal gels are purely elastic for small deformations, where both aero- A nd hydrogels show similar mechanical properties. The comparison of the absolute value of the shear modulus reveals that these gels are significantly softer than that estimated by standard cellular solid models. When increasing the particle concentration through a compression of the sample, the modulus increases in a power law-like behavior similar to the prediction of diffusion limited cluster aggregation. We verify the mechanical heterogeneities resulting from the aggregation process using colloidal probe atomic force microscopy (AFM), where both methods provided comparable absolute values of the mechanical properties. The differences between these methods can be explained by the local and global way of determining the mechanical properties.
CRIS-Team Scopus Importer:2022-04-14